2015
DOI: 10.5194/amt-8-633-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of cloud heterogeneities on cirrus optical properties retrieved from space-based thermal infrared radiometry

Abstract: Abstract. This paper presents a study, based on simulations, of the impact of cirrus cloud heterogeneities on the retrieval of cloud parameters (optical thickness and effective diameter) for the Imaging Infrared Radiometer (IIR) on board CALIPSO. Cirrus clouds are generated by the stochastic model 3DCLOUD for two different cloud fields and for several averaged cloud parameters. One cloud field is obtained from a cirrus observed on 25 May 2007 during the airborne campaign CIRCLE-2 and the other is a cirrus unci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 46 publications
(96 reference statements)
1
41
0
Order By: Relevance
“…In this study, we assume that TOA brightness temperature differences between BT computation assuming 1-D RT inside a homogeneous pixel and 3-D RT inside a heterogeneous pixel depend on two effects: (i) the optical thickness horizontal inhomogeneity leading to the planeparallel approximation bias and the (ii) horizontal radiative transport effect due to the independent pixel approximation error. The cloud vertical heterogeneities of optical properties are neglected here, based on the findings of Fauchez et al (2014Fauchez et al ( , 2015. As previous studies already showed, the PPHB is the larger heterogeneity effect for nadir observations at the typical spatial resolution of polar orbiters such as AIRS, MODIS or IIR.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, we assume that TOA brightness temperature differences between BT computation assuming 1-D RT inside a homogeneous pixel and 3-D RT inside a heterogeneous pixel depend on two effects: (i) the optical thickness horizontal inhomogeneity leading to the planeparallel approximation bias and the (ii) horizontal radiative transport effect due to the independent pixel approximation error. The cloud vertical heterogeneities of optical properties are neglected here, based on the findings of Fauchez et al (2014Fauchez et al ( , 2015. As previous studies already showed, the PPHB is the larger heterogeneity effect for nadir observations at the typical spatial resolution of polar orbiters such as AIRS, MODIS or IIR.…”
Section: Discussionmentioning
confidence: 98%
“…Concerning infrared (IR) radiances or brightness temperatures (BTs), Fauchez et al (2012Fauchez et al ( , 2014 show that heterogeneity effects can significantly influence cirrus optical property retrievals at the 1 km scale of IIR thermal infrared observations, with potentially more than +10 K on TOA BT for heterogeneous pixels, depending also on the cloud altitude. Fauchez et al (2015) also show that these TOA BT effects result in an overestimate of the retrieved effective diameter by more than 50 % for small crystals (CED under 20 µm) and underestimate the retrieved optical thickness by up to 25 %. These errors could significantly influence the cirrus feedbacks assumed in global atmospheric models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fauchez et al, 2015), errors that arise from a lack of precision, accuracy, or incomplete sampling in the atmospheric and surface state (e.g. Kahn et al, 2015), variability in mixtures of ice crystal habits and PSDs within a single satellite pixel (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At 1 km pixel size, they found significant errors ranging between -0.3% to 14% (-5% to 30%) from nadir (oblique view) depending on the cloud heterogeneity. Some recent studies were also made in case of ice clouds and found non negligible errors on retrieved COT from IR measurements 10 (Fauchez et al, 2015) or from visible and near-infrared measurements (Zhou et al, 2017) In this paper, we investigate the impact of cloud heterogeneities on retrieved parameters on observations from the POLarization and Directionality of Earth Reflectance radiometer, POLDER, which was on board the platforms ADEOS1 in 1999, ADEOS2 in 2002and PARASOL between 2005. POLDER/PARASOL allows to measure multi-angular 15 total reflectances from 443 to 1020 nm and multi-angular polarized reflectances for three channels (490, 670 and 865 nm).…”
Section: Introductionmentioning
confidence: 99%